Quantitative flow ratio-guided versus angiography-guided operation for valve disease accompanying coronary heart disease - Yan, Wenlong; Wang, Yangyang; Zheng, Xin; Guo, Pengfei; Yang, Sumin (Frontiers in Cardiovascular Medicine, 2023)
Abstract Background: Valve replacement combined with coronary artery bypass graft (CABG) operation (VR + CABG) is usually associated with higher mortality and complication rates. Currently, angiography remains the most commonly used approach to guide CABG. The aim of this study is to investigate whether a quantitative flow ratio (QFR)-guided strategy can improve the clinical outcomes of VR + CABG. Methods: Patients (n = 536) treated by VR + CABG between January 2018 and December 2021 were retrospectively assessed. In 116 patients, all lesions were revascularized entirely based on QFR (the QFR-guided group), whereas in 420 patients, all lesions were revascularized entirely based on angiography (the angiography-guided group). To minimize selection bias between the 2 groups, propensity score matching was performed at a ratio of 1:2. The primary endpoint of the study was the rate of major adverse cardiac and cerebrovascular events (MACCE) at 1-year, which was defined as a composite of cardiac mortality, myocardial infarction (MI), any repeat revascularization, and stroke. Results: No statistically significant differences were observed in the baseline clinical characteristics between the QFR-guided and angiography-guided groups after propensity score matching. When compared with the angiography-guided group, the QFR-guided group had a significantly shorter operative time (323 ± 60 min vs. 343 ± 71 min, P = 0.010), extra corporal circulation time (137 ± 38 min vs. 155 ± 62 min, P = 0.004), clamp time (73 ± 19 min vs. 81 ± 18 min, P < 0.001), and less intraoperative bleeding volume (640 ± 148 mL vs. 682 ± 166 mL, P = 0.022). Compared with the angiography-guided group, the 1-year MACCE was significantly lower in the QFR-guided group (6.9% vs. 14.7%, P = 0.036, hazard ratio = 0.455, 95% confidence interval: 0.211–0.982). Conclusions: Our results raise the hypothesis that among patients who undergo VR + CABG, QFR-guided strategy is associated with optimized surgical procedure and a superior clinical outcome, as evidenced by a lower rate of MACCE at 1-year compared with conventional angiography-guided strategy.